Internal control in the system of administrative management decisions - Kovalchuk, Svitlana (Management and Entrepreneurship: Trends of Development, 2018)
Purpose. The paper purpose is to expand the interpretation of the concept of “internal control” beyond the traditional understanding and to justify its capabilities and significance in the system of making managerial decisions, not only as a tool for checking past information, but also as a means of evaluating each decision at the stage of its adoption. Approach. The basic methods of research are general scientific methods of cognition: comparison, theoretical substantiation, methods of generalization and systematization, etc. Findings. The subject of the article is theoretical approaches to the interpretation of the essence of internal control and its types. The article covers approaches to the interpretation of the essence of internal control. It is substantiated that the two directions are distinguished in internal control: retrospective and perspective. The basic tasks of retrospective and perspective internal control are defined. It is noted that promising internal control is aimed at verifying the economic feasibility and legality of management decisions. The expediency of fulfilling perspective internal control in the enterprise management system is substantiated. Implications. Perspective internal control is carried out in the process of direct acceptance of managerial decisions as a tool for their assessment and substantiation. It allows you to choose the best solution from alternative options. This reduces the risks of unproductive losses, crisis consequences for the financial condition of the enterprise. Originality. Retrospective and promising internal control will maximize the need for modern enterprises in high-quality, verified information. Perspective internal control will provide the opportunity to minimize mistakes and ineffective decisions at the stage of their adoption.